2013
DOI: 10.1371/journal.pone.0059914
|View full text |Cite
|
Sign up to set email alerts
|

Stylet Morphometrics and Citrus Leaf Vein Structure in Relation to Feeding Behavior of the Asian Citrus Psyllid Diaphorina citri, Vector of Citrus Huanglongbing Bacterium

Abstract: The Asian citrus psyllid (ACP), Diaphorina citri (Hemiptera: Psyllidae), is the primary vector of the phloem-limited bacterium Candidatus Liberibacter asiaticus (LAS) associated with huanglongbing (HLB, citrus greening), considered the world’s most serious disease of citrus. Stylet morphometrics of ACP nymphs and adults were studied in relation to citrus vein structure and to their putative (histologically verified) feeding sites on Valencia orange leaves. ACP nymphs preferred to settle and feed on the lower (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 28 publications
(72 reference statements)
3
58
0
3
Order By: Relevance
“…The diameters of the different nymphal instar stylet bundle food canals are expected to become consecutively larger with each (increasing) developmental stage. The diameter of the adult stylet food canal has been estimated by TEM as approximately 0.818 µm (Ammar et al 2013), 0.6 µm (Cicero et al 2015), and 0.9 µm (Garzo et al 2012). Given this range in size, a predicted minimum threshold diameter by which CLso ingestion could occur would seem possible after stylet biogenesis during the pharate third instar.…”
Section: Discussionmentioning
confidence: 99%
“…The diameters of the different nymphal instar stylet bundle food canals are expected to become consecutively larger with each (increasing) developmental stage. The diameter of the adult stylet food canal has been estimated by TEM as approximately 0.818 µm (Ammar et al 2013), 0.6 µm (Cicero et al 2015), and 0.9 µm (Garzo et al 2012). Given this range in size, a predicted minimum threshold diameter by which CLso ingestion could occur would seem possible after stylet biogenesis during the pharate third instar.…”
Section: Discussionmentioning
confidence: 99%
“…citri nymphs and adults that reached a vascular bundle were associated with the phloem, whereas 10–20% were associated with xylem vessels [15]. A fibrous ring of thick-walled sclerenchyma fibers around the phloem in citrus leaves was shown to be more prominent (thicker, with more layers) in fully expanded mature leaves compared with younger leaves, especially on the lower (abaxial) side compared with the adaxial side, and in the midrib compared with secondary veins [15]. In a subsequent study [16], the fibrous ring in the midrib was found to be significantly thicker in one citrus accession (UN-3881) that is relatively resistant to D .…”
Section: Introductionmentioning
confidence: 99%
“…La respuesta a estos ataques del insecto requiere un mecanismo integrado donde las señales internas y externas de la planta detectan y ocasionan una reacción apropiada en la planta (Stepanova et al, 2005). El insecto en estado de ninfa y adulto se caracteriza por tener un estilete que inserta en la lámina foliar para alimentarse, lo que provoca daño celular con la fractura inter e intracelular (daño mecánico) que induce estrés biótico (Ammar et al, 2013).…”
Section: Introductionunclassified
“…Estos procesos de defensa se han estudiado en diversos modelos, algunos en cítricos donde estudian el daño causado por el estilete de las ninfas de Diaphorina citri, que es el sitio de alimentación (Ammar et al, 2013). En el caso de las gramíneas existen estudios en maíz donde se observó la acumulación de calosa por presencia de aluminio debido a la exposición que tienen las raíces a dicho elemento que les induce la expresión de un daño (Arcos y Narro, 2009).…”
Section: Introductionunclassified